A Model of Online Protection to Reduce Children’s Online Risk Exposure: Empirical Evidence From Asia. - Teimouri, Misha; Benrazavi, Seyed Rahim; Griffiths, Mark D.; Hassan, Md Salleh (Sexuality & Culture, 2018)
Children are surrounded by a variety of digital media and are exposed to potential risks that come with such easy accessibility. Learning how to be safe online is an important consideration for both children and their caregivers. The present study proposes an integrated model of online safety based on constructs from protection motivation theory and the health belief model, namely perceived severity of (and susceptibility to) risk, online self-efficacy, online privacy concern, and digital literacy. The study comprised a survey conducted among 420 schoolchildren aged 9-16 years. Using partial least squares-structural equation modelling, the results illustrated the presence of a negative effect of ‘perceived severity of online risk’ toward online risks, whereas the effect of ‘digital literacy’ was found to be positive. Children whose perception of online risks was more severe were less exposed to online risks if they had higher ‘online privacy concerns’ than the children with higher ‘digital literacy’ who are more exposed to online risk. Results of the study show that engaging in safe online behaviour requires children to have a high perception regarding severity of online risks as well as knowledge of online privacy concerns. Online risks and opportunities occur in parallel. Consequently, the factors that increase or decrease risk may also increase or decrease the benefits.